Studi Kasus: Gangguan Afektif Bipolar Kini Depresi Disertai Anxietas Pada Anak Dengan Komorbiditas Ibu Gangguan Afektif - Tia Mardiati; Andri Sudjatmoko (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Depression is a mental health disorder that often occurs in children and adolescents. Cases of depression are often not properly diagnosed. Surveys on mental health in children and adolescents tend to increase annually, because cases of depression in children are not considered a threat by the most people. Cases of depression in children and adolescents are also closely related to genetic factors, in addition to environmental factors. Parents that suffering from depression disorders increase the risk of their children suffering from depression. Therefore, this study was conducted to examine the relationship between children with depression and parents who have a history of depression. The study was conducted based on a case study, using a sample of pediatric outpatients at the Mental Health Clinic of Gading Medika Hospital. The patient suffered from depression and had been receiving regular treatment at the Mental Health Clinic of Gading Medika Hospital, whose mother was also a regular patient at the Mental Health Clinic of Gading Medika Hospital with a history of depression. After one year of regular treatment, the symptoms are reduced. The patient initially received antidepressant therapy in the form of sertraline, and to address mood disorders such as anxiety and panic attacks, Clobazam and Cognitive Behavioral Therapy (CBT) were given. After one year of treatment, the patient switched to Clobazam and CBT alone. The patient's results showed improvement, reducing her symptoms of depression and panic disorder.